Influence of a tapered cylinder nozzle on pressure pulsations in a variable high-speed reciprocating compressor piping system. (June 2017) - Liu, Zhan; Wang, Zengli; Feng, Quanke; Yu, Xiaoling
This paper investigates the influence of a tapered cylinder nozzle (TCN) on pressure pulsations in a high-speed reciprocating compressor piping system. Numerical methods, the 3D frequency-domain finite element method (FEM) and the 3D time-domain computational fluid dynamics (CFD) were used to separately calculate gas column natural frequencies and pressure pulsations. With favorable agreement between model predictions and experimental data, it is concluded from predictions that an installed TCN changes both the values and distribution of frequencies because installation of a TCN filter can alter gas column structure in the piping system. The order of frequency dominated by cylinder nozzle response increases sharply as the TCN diameter ratio increases and the TCN length to diameter ratio decreases. Pressure fluctuations can be effectively attenuated in piping system under different functioning conditions, e.g. variable compressor speeds and variable discharge pressures.